Pengembangan Model Pembelajaran Konsep Bilangan Bagi Anak Dengan Mathematics Learning Disability di Sekolah Dasar Inklusi - Erna Suwangsih; Hafiziani Eka Putri; Suprih Widodo; Trisno Ikhwanudin (IndoMath: Indonesia Mathematics Education, 2018)
This research is motivated by the need for effective mathematical learning models for students with learning difficulties in math at inclusion schools. The formulation of the problem is "How can the learning model that can be used to help the child the difficulty learning math in understanding the concept of numbers?". This research uses Reseach and development method. Research data obtained from the results of student tests and observation of student and teacher interaction. This research produced a model of mathematics learning design for students with learning difficulties. The conclusion is that (1) Mathematics learning model can improve students' understanding about addition and reduction of three numbers, because in general the learning achievement of students before and after learning differ significantly. (2) Learning that takes place more centered on the students (student center), because the student activity is greater than the teacher activity. (3) The use of students' mathematics teaching aids increases from one to two meetings. (4) The students' response to the Mathematics learning model is positive.